Factors Associated with Outpatient Waiting Times at Oesapa Health Center - Mesah, Indri Melanie; Sirait, Rina Waty; Sinaga, Masrida (Universitas Nusa Cendana, 2023)
The standard waiting time for medical services is 60 minutes, starting from the registration process to the time when patients enter the doctor's examination room. Long wait periods can aggravate patients' condition when they need a doctor's consultation and this impacts the health service quality offered by primary health care. The Oesapa Health Center was visited by 150 patients every day on average. Based on interviews with several patients, they had to wait 1-2 hours to receive service. This study aims to identify variables influencing the health center's outpatient waiting time in 2022. The cross-sectional research method was applied. The research sample consisted of 93 people selected by accidental sampling. Data collection used questionnaires and observation sheets. The data analysis was bivariate using the chi-square test. The results showed a relationship between the technical competence of health workers, timeliness of service, and facility and infrastructure availability with the waiting time for outpatients at the center. Puskesmas Oesapa needs to focus more on the service promptness, coordination among the staff, and ensuring the center equipped with needed facilities to speed up services and reduce patient waiting times.